Design specification of context cognitive trust evaluation model for v2v communication in iov - Rehman, A. (Springer, 2020)
VANET (Vehicle Ad Hoc Network) is now making its shift towards IoV (Internet of Vehicle). On road smart vehicles are expected to be the part of vehicle network in near future. Information integrity during V2V (Vehicle to Vehicle) communication is one of the key barriers in the implementation of vehicle networks. Vehicle networks face many drastic changes in the network topology during a short period of time. Absolute central network availability is difficult in vehicular networks that makes V2V communication significantly important. Trustworthiness plays a very important role to ensure integrity. Many models of trust evaluation have been proposed with a common trait of fixed nature. As possibility of scenario change is high for every other event so the fixed nature of previous models seems impractical. Our work aims to solve the problem by introducing context awareness between the available information and trust evaluation. It is expected that the proposed solution will overcome the limitations of current models and provide a hybrid adaptive model. Our model is based on context scenario adaptation rather than depending on a limited set of situations. Â© Springer Nature Switzerland AG 2020.